The Impact of COVID-19 on Anxiety in Chinese University Students - Wang, Chongying; Zhao, Hong (Frontiers in Psychology, 2020)
COVID-19 had become a pandemic raising concerns of widespread panic and increasing anxiety and stress in individuals all over the world (WHO, 2020). Lots of countries had closed their schools. As the first country to do so, Chinese colleges and universities were making use of different modes of learning, including online-learning based on different platforms to achieve the goal suggested by Ministry of Education in China, “suspending classes without suspending learning”, since middle February. This paper is the first one which aims to investigate the anxiety of Chinese university students after the outbreak of COVID-19 right before the start of new spring term. 3611 university students (female: male = 1.48:1) aged between 18 to 24 from all over China were enrolled to this study from a top university in China. The Self-Rating Anxiety Scale – SAS (Zung, 1971) was used to assess anxiety two days before the start of new spring term in middle February. All four-year undergraduate students were included in the study. The mean SAS score was 40.53 (SD = 10.15), significantly higher than the national norm (Mean = 29.78, SD = 10.07, p =<.001), and there were still 557 (15.43%, Mean = 58.75, SD = 8.9) students met the cutoff of 50 and were screened positive. Comparisons among sexes, grades and majors were also conducted. Significant differences were found between all males and all female (p =<.001), and between all students majoring arts and sciences in the anxiety sample (n = 557, p = 0.05). The results also showed that the mean SAS scores were not correlated with the regions they came from / lived in. This study concluded that the Chinese university students showed higher anxiety for COVID-19.